2015
DOI: 10.1186/s12916-015-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Hygiene Hypothesis of helminthes and autoimmunity: origins, pathophysiology, and clinical applications

Abstract: BackgroundThe Hygiene Hypothesis (HH) attributes the dramatic increase in autoimmune and allergic diseases observed in recent decades in Western countries to the reduced exposure to diverse immunoregulatory infectious agents. This theory has since largely been supported by strong epidemiological and experimental evidence.DiscussionThe analysis of these data along with the evolution of the Western world’s microbiome enable us to obtain greater insight into microorganisms involved in the HH, as well as their reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 187 publications
3
121
0
10
Order By: Relevance
“…65,66 Effective translation to help address the unmet need of allergy and asthma prevention in human health has been elusive. Compelling scientific leads have been followed in randomized clinical trials without significant benefit for patients and doctors in airways allergy and asthma clinics.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Effective translation to help address the unmet need of allergy and asthma prevention in human health has been elusive. Compelling scientific leads have been followed in randomized clinical trials without significant benefit for patients and doctors in airways allergy and asthma clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A hygienic lifestyle can also lead to decreased exposure to indigenous viruses such as Hepatitis A, pathogenic bacteria such as Heliobacter pylori, Salmonella spp., Mycobacterium tuberculosis , and parasites like helminths and Toxoplasma gondii (19). Anecdotal evidence has shown that parasitic infection diminishes or eliminates allergic reactions (11) probably because helminths can modulate the gut microbiota and DCs toward a more tolerogenic phenotype (20). For example, Nod2 knockout (KO) mice showed that intestinal helminth infection prevented the colonization of inflammatory Bacteriodes vulgatus and promoted the colonization of protective microbiota enriched in Clostridiales, which was caused by a T helper cell type 2 immune response (21).…”
Section: Discussionmentioning
confidence: 99%
“…Infections that might confer a protective effect to the host are colonizations of the GIT by parasitic worms. Different studies have shown that helminths may affect the host’s immune response by the promotion of an anti-inflammatory environment [85, 86]. Based on this, the possibility of treating MS with helminths has already been explored in animal models [8789] and also phase 1 clinical trials [90].…”
Section: Environment and Its Link To Msmentioning
confidence: 99%